Experiments and finite element analysis on a hybrid polymer gear rack. (August 2023) - Hooton, James D.S.; Gonçalves, David E.P.; Fernandes, Carlos M.C.G.
Abstract: This article presents the results of experiments and finite element analysis on a hybrid polymer gear concept. The study aimed to investigate the effectiveness of the hybrid gear concept by using a rack tooth geometry. The results of the experiments have shown that the hybrid gear concept improves the heat evacuation from the flank and root regions, potentially increasing the load-carrying capacity. Additionally, the results of the experiments were compared with those obtained from the finite element analysis to validate the numerical model. The results showed that the hybrid polymer gear rack exhibited good thermal performance, and the finite element analysis accurately predicted the behaviour of the gear rack specimens. The study also analyses the influence of the interference fit on the contact pressure and thermal contact conductance in a hybrid polymer gear concept, taking into account surface roughness and temperature. It provides insights for optimizing the press fit to ensure efficient heat dissipation in practical applications. Overall, the study provides valuable insights into the potential use of hybrid polymer–metal materials in gear applications and supports the validity of the hybrid gear concept. Graphical abstract: